Review of Adaptive Management Approaches - Twine, Edgar E.; Ndindeng, Sali Atanga (Africa Rice Center, 2025)
Despite CGIAR’s efforts to implement the Pause & Reflect adaptive management approach, barriers to uniform application exist, necessitating a unified adaptive management protocol to optimize engagement and impact across programs. The review examines adaptive management, emphasizing its flexible, learning-based practices across complex environments. Two main schools of thought are identified: the Resilience-Experimentalist School and the Decision Theoretic School. The former focuses on stakeholder collaboration, ecological models, and collective learning, emphasizing adaptability in complex systems through practices like Active Adaptive Management and Scenario Planning. This approach encourages resilience and utilizes institutional dynamics for transformation. Conversely, the Decision-Theoretic School employs structured decision-making and quantitative models, predominantly prioritizing predefined objectives and optimization under uncertainty. Approaches such as Structured Decision Making and Bayesian Adaptive Management characterize this school, advocating clarity and probabilistic reasoning. Key findings include the significance of organizational flexibility and participatory planning, iterative learning, and continuous monitoring across various case studies. The review highlights that while both schools aim to enhance management efficacy through iterative learning, Resilience-Experimentalist methods may better fit CGIAR's programs due to the methods’ adaptability to complex and uncertain situations. We conclude that blending insights from both schools can foster a more robust adaptive management framework.